1991
DOI: 10.2527/1991.692726x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of sodium zeolite-A and copper in growing swine: growth, and bone and tissue mineral concentrations.

Abstract: An experiment was conducted with 64 crossbred pigs to determine the effect of 0 or .50% dietary sodium zeolite-A (NZA) in combination with 0 or 250 ppm supplemental Cu (as CuSO4.5H2O). Pigs were assigned randomly to one of the following four treatments: 1) corn-soybean meal basal (B), 2) B + .50% NZA, 3) B + 250 ppm Cu, or 4) B + .50% NZA + 250 ppm Cu. Each treatment was replicated four times with four pigs per replicate. Average initial weight was 7.5 kg and the experimental period lasted 144 d. Overall rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
24
2
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 0 publications
7
24
2
3
Order By: Relevance
“…However, in the finishing phase clinoptilolite decreased weight gain. The feed conversion ratio was unaffected by dietary supplementation of Cp and these results are in accordance with those of Pond et al (1988) and Ward et al (1991). The magnesium silicate sepiolite could prolong the retention time of digesta in the gut of pigs and poultry (Ouhida et al, 2000).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, in the finishing phase clinoptilolite decreased weight gain. The feed conversion ratio was unaffected by dietary supplementation of Cp and these results are in accordance with those of Pond et al (1988) and Ward et al (1991). The magnesium silicate sepiolite could prolong the retention time of digesta in the gut of pigs and poultry (Ouhida et al, 2000).…”
Section: Discussionsupporting
confidence: 81%
“…Vrzgula and Bartko (1984) and Pond et al (1988) found that weight gain improved when clinoptilolite was added to the feed. Contrary to these results, some other authors (Shurson et al, 1984;Ward et al, 1991;Poulsen and Oksbjerg, 1995) found that body weight gain was unaffected by clinoptilolite. In the present study the oral administration of clinoptilolite was found to have positive effects on growth performance during the growing phase of the pigs.…”
Section: Discussioncontrasting
confidence: 52%
“…Similarly, the supplementation of the diets with Cp did not result in any alteration in serum Ca and P concentrations, in agreement with previously reported observations in growing pigs (Vrzgula and Bartko, 1984;Yannakopoulos et al, 2000), broilers (Dwyer et al, 1997) and dairy cows (Katsoulos et al, 2005). It is worth noting that the reducing effect of sodium zeolite A on serum P concentration, as it has been demonstrated in other studies (Shurson et al, 1984;Ward et al, 1991), was attributed to the formation of insoluble phosphates after the interference of P with the Al ions removed from the degraded zeolitic material. Zeolites' stability in acid solutions is mainly controlled by the Si/Al ratio of the structure.…”
Section: Discussionsupporting
confidence: 80%
“…It was observed that especially Ca 2+ and K + fluctuated significantly in copper groups. Similar results were reported from a study where zeolite was used (Ward et al, 1991). It has clearly been shown in many researches that the zeolite-added feeds have contributed to the health status, feed efficiency, and growth rates.…”
Section: Discussionsupporting
confidence: 79%